Research of neutron interaction with matter under high density interaction. Part II. The experimental research dependence of neutron cross section from density interactions - Yu. G. Shchepkin; V. I. Slisenko; E. A. Pavlenko; T. A. Kostyuk (Ядерна фізика та енергетика)
Research of neutron interactions with the matter under density interactions (DI) up to ~109 cm-2 · s-1, were provided with aim of revelation of possible dependence neutron cross section from DI. The method of research [1] for revelation of such dependence was improved [2]. It consists on transmission asymmetry (TA) of neutrons measurement through of samples pair from different matters. TA was revealed for all pairs containing 235U, in particularly, for pair (235U - Cd) TA consists of (2,541 ± 0,294) ∙ 10-4 that does not contradict to assumption of the cross section dependence from DI. It was defined that correlation related with fission of 235U, and corresponding of relative change of the effective neutron cross section equals ~2,6 ∙ 10-4. Analysis shows that observed depend-ence may be treated as the result of secondary states composition of 235U with anomaly great values of neutron cross section, yield, reduced of possibility radioactive transition and small energy, excited by fragment fission.